TRENDS AND DETERMINANTS OF POLISH SUPPORT TERRITORIAL COOPERATION IN TOURISM - Wiatrak, Andrzej (Acta Scientiarum Polonorum. Oeconomia, 2010)
In this article the following topics were discussed: directions of tourism development in the light of Polish developing plans, directions of tourism development in border regions, development of tourism resulting from the transnational and interregional cooperation and development of tourism between the regions and districts in Poland. The aim of this article – based on literature, documents of tourism development in Poland and selected instruments structural policy of the European Union – was to present the directions of this cooperation and determinants of realization in Poland in the current financial perspective. Moreover was indicated to support of this cooperation.